An Appraisal of Selected Brass Products from Krofofrom Ashanti-Ghana - Asante, Eric Appau; Effah, Oppong Christopher; Kissi, Samuel Baah (International Journal of Natural Sciences Research, 2019)
In the Asante kingdom, evidence of the use of metals like gold, silver and brass are actively displayed in all aspects of their socio-cultural lives, be it for beautification and other art forms. There are a lot of beautiful cultural elements encoded in the designs and the production of brass casting at Krofofrom in Asante. However, very little attention has been given to them. The main objective of this article is to appraise selected brass products at Krofofrom in Ashanti. It further goes on to examine the production processes of brass casting at Krofofrom and the aesthetics of the brass products as well. The brass casting in Krofofrom is well known and unique; this is because it embodies a lot of history and the cultural heritage of the people, which is portrayed in visual art forms. These art forms have a lot of aesthetic appeals if analyzed. Descriptive method of qualitative research approach with interviews and observations as instruments were employed. Secondary data was obtained from books, journals and the internet.